Impact of Periodontal Disease on the Quality of Life of Diabetics Based on Different Clinical Diagnostic Criteria - Aline Mendes Silva de Pinho; Carolina Marques Borges; Mauro Henrique Nogueira Guimarães de Abreu; Efigênia Ferreira e Ferreira; Andréa Maria Duarte Vargas (International Journal of Dentistry)
The aim of this study was to determine the impact of periodontal disease on the quality of life of individuals with diabetes according to different clinical criteria (I-AAP, II-Beck, III-Machtei, IV-Lopez, V-Albandar, VI-Tonetti, and VII-CPI). This cross-sectional study sampled 300 individuals in Belo Horizonte, Brazil. The Oral Health Impact Profile was used to measure the impact of periodontal disease on quality of life. Prevalence of periodontal disease was 35.3%, 30.7%, 35.0%, 9.7%, 92.3%, 25.3%, and 75.3% using criteria I, II, III, IV, V, VI, and VII, respectively. The III-Machtei (P=0.043) and IV-Lopez (P<0.001) criteria were associated with OHIP-14; functional limitation was associated with IV-Lopez (P=0.006) and V-Albandar (P=0.018) criteria. Pain was only associated with V-Albandar criteria (P<0.001). Psychological discomfort was associated with the IV-Lopez (P=0.018) criteria. Physical disability was associated with the IV-Lopez (P=0.047) and V-Tonetti (P=0.046) criteria. Being handicapped was associated with the I-AAP (P=0.025) and II-Beck (P=0.041) criteria. Concepts of health and disease determined by clinical diagnostic criteria may influence the assessment of the impact of periodontal disease on diabetics' quality of life.